2018
DOI: 10.1037/cap0000158
|View full text |Cite
|
Sign up to set email alerts
|

Putting recommendations into practice: Improving psychological services in rural and northern Canada.

Abstract: Recent publications (i.e., Chodos, 2017;Peachy, Hicks, & Adams, 2013) have made many recommendations for improving access to psychological services for all Canadians but lack a focus on rural and northern (R&N) populations. Limited access to psychologists' expertise is demonstrable in R&N regions, where resources are particularly strained. This article examines the recommendations through the lens of the R&N psychologist, including those that aim to change existing service delivery models and increase funding.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Our study, however, identified numerous challenges faced by social workers following the rapid transition to virtual care. One major barrier experienced by some of our participants had to do with limited access to high to stable high-speed Internet for those residing in rural and remote communities ( Lints-Martindale et al , 2018 ; Baylak et al , 2020 ). Despite some improvements over the last decade ( Jong et al , 2019 ), achieving social work’s grand challenge to improve practice innovation ( Berzin et al , 2015 ) through technology requires further commitment by policy makers to ensure equitable access to consistent high-speed Internet access rural and remote geographical regions ( Lints-Martindale et al , 2018 ; Baylak et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study, however, identified numerous challenges faced by social workers following the rapid transition to virtual care. One major barrier experienced by some of our participants had to do with limited access to high to stable high-speed Internet for those residing in rural and remote communities ( Lints-Martindale et al , 2018 ; Baylak et al , 2020 ). Despite some improvements over the last decade ( Jong et al , 2019 ), achieving social work’s grand challenge to improve practice innovation ( Berzin et al , 2015 ) through technology requires further commitment by policy makers to ensure equitable access to consistent high-speed Internet access rural and remote geographical regions ( Lints-Martindale et al , 2018 ; Baylak et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…One major barrier experienced by some of our participants had to do with limited access to high to stable high-speed Internet for those residing in rural and remote communities ( Lints-Martindale et al , 2018 ; Baylak et al , 2020 ). Despite some improvements over the last decade ( Jong et al , 2019 ), achieving social work’s grand challenge to improve practice innovation ( Berzin et al , 2015 ) through technology requires further commitment by policy makers to ensure equitable access to consistent high-speed Internet access rural and remote geographical regions ( Lints-Martindale et al , 2018 ; Baylak et al , 2020 ). Additionally, our participants have expressed great concerns about the adaptations of social work practice to virtual care so as not to negate the relational nature of social work practice.…”
Section: Discussionmentioning
confidence: 99%
“…When asked about the anticipated future of virtual care, participants in our study expressed concerns that virtual care will continue for some patients, yet connectivity difficulties in certain geographical regions will create access barriers for other patients. Limited access to stable high-speed internet may disadvantage patients residing in rural and remote communities ( Baylak et al 2020 ; Lints-Martindale et al 2018 ). Despite some improvements over the past decade ( Jong et al 2019 ), commitment by policy makers to ensure equitable access to consistent high-speed internet access in rural and remote geographical regions is needed to sustain virtual care ( Baylak et al 2020 ; Lints-Martindale et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Limited access to stable high-speed internet may disadvantage patients residing in rural and remote communities ( Baylak et al 2020 ; Lints-Martindale et al 2018 ). Despite some improvements over the past decade ( Jong et al 2019 ), commitment by policy makers to ensure equitable access to consistent high-speed internet access in rural and remote geographical regions is needed to sustain virtual care ( Baylak et al 2020 ; Lints-Martindale et al 2018 ). Moreover, protocols and guidelines developed in the primary care team context can help shape the future of virtual care so that the delivery of care aligns with patients' care needs.…”
Section: Discussionmentioning
confidence: 99%
“…However, these types of programs tend to be costly (Anderson et al, 2017) and are not available in all rural areas (Turk-Adawi et al, 2014). Additional barriers to telehealth in rural areas include limited access to highspeed internet (Lints-Martindale et al, 2018) and lack of provider utilization (Taylor et al, 2015).…”
Section: Discussionmentioning
confidence: 99%